The other side of cardiac Ca2+ signaling: transcriptional control - Domínguez-Rodríquez, Alejandro; Ruiz-Hurtado, Gema; Benitah, Jean-Pierre; Gomez, Ana M. (Frontiers in Physiology, 2012)
Ca2+ is probably the most versatile signal transduction element used by all cell types. In the heart, it is essential to activate cellular contraction in each heartbeat. Nevertheless Ca2+ is not only a key element in excitation-contraction coupling (EC coupling), but it is also a pivotal second messenger in cardiac signal transduction, being able to control processes such as excitability, metabolism, and transcriptional regulation. Regarding the latter, Ca2+ activates Ca2+-dependent transcription factors by a process called excitation-transcription coupling (ET coupling). ET coupling is an integrated process by which the common signaling pathways that regulate EC coupling activate transcription factors. Although ET coupling has been extensively studied in neurons and other cell types, less is known in cardiac muscle. Some hints have been found in studies on the development of cardiac hypertrophy, where two Ca2+-dependent enzymes are key actors: Ca2+/Calmodulin kinase II (CaMKII) and phosphatase calcineurin, both of which are activated by the complex Ca2+/ /Calmodulin. The question now is how ET coupling occurs in cardiomyocytes, where intracellular Ca2+ is continuously oscillating. In this focused review, we will draw attention to location of Ca2+ signaling: intranuclear ([Ca2+]n) or cytoplasmic ([Ca2+]c), and the specific ionic channels involved in the activation of cardiac ET coupling. Specifically, we will highlight the role of the 1,4,5 inositol triphosphate receptors (IP3Rs) in the elevation of [Ca2+]n levels, which are important to locally activate CaMKII, and the role of transient receptor potential channels canonical (TRPCs) in [Ca2+]c, needed to activate calcineurin.